International Consensus on Evidence Gaps and Research Opportunities in Extracorporeal Cardiopulmonary Resuscitation for Refractory Out-of-Hospital Cardiac Arrest: A Report From the National Heart, Lung, and Blood Institute Workshop - Morrison, Laurie J; Hunt, Elizabeth A; Grunau, Brian; Aufderheide, Thomas P; Callaway, Clifton; Tonna, Joseph E; Sasson, Comilla; Blewer, Audrey; McNally, Bryan F; Yannopoulos, Demetris; Belohlavek, Jan; Bartos, Jason; et al. (Journal of the American Heart Association, 2025)
The increased accessibility of extracorporeal membrane oxygenation following the COVID-19 pandemic and the publication of the first randomized trial of extracorporeal cardiopulmonary resuscitation (ECPR) prompted the National Heart, Lung, and Blood Institute to sponsor a workshop on ECPR. Two more randomized trials have since been published in 2022 and 2023. Based on the combined findings and review of the evidence, an international panel of authors identified gaps in science, inequities in care and diversity in outcomes, and suggested research opportunities and next steps. The science pertaining to ECPR would benefit from the United States contributing uniform data to existing registries and sharing common data with the ELSO (Extracorporeal Life Support Organization) international registry to increase the sample size for observational research. In addition, well-designed efficacy trials, recruiting across different regions of care evaluating long-term follow-up, including patient reported outcomes, cost effectiveness, and equity measures, would contribute significantly to the body of science. Workshop participants defined the population of patients with out-of-hospital cardiac arrest most likely to benefit from ECPR. ECPR-eligible patients include those aged 18 to 75 years functioning independently without comorbidity; before suffering a witnessed out-of-hospital cardiac arrest and without any obvious cause of the cardiac arrest; presenting in a shockable rhythm and transported with mechanical cardiopulmonary resuscitation to an ECPR-capable institute within 30 minutes, which is recommended after 3 rounds of advanced life support treatment without return of spontaneous circulation. There are significant inequities in out-of-hospital cardiac arrest care that need to be addressed such that outcomes are optimized for each target region before implementing ECPR in a clinical or implementation trial.
Keywords: Extracorporeal Membrane Oxygenation; zástava srdce mimo nemocnici; Out-of-Hospital Cardiac Arrest; konsensus; COVID-19; mezery v důkazech; Spojené státy americké; Consensus; Humans; National Heart, Lung, and Blood Institute (U.S.); SARS-CoV-2; lidé; kardiopulmonální resuscitace; mimotělní membránová oxygenace; Cardiopulmonary Resuscitation; United States; Evidence Gaps